A new method to trace three-dimensional magnetic field structure within molecular clouds using dust polarization. Issue 3 (4th March 2019) - Chen, Che-Yu; King, Patrick K; Li, Zhi-Yun; Fissel, Laura M; Mazzei, Renato R
Abstract: The complete three-dimensional structure of the magnetic field within molecular clouds has eluded determination despite its high value in determining controlling factors in the star formation process, as it cannot be directly probed observationally. Considering that inclination of the magnetic field relative to the plane of sky is one of the major sources of depolarization of thermal emission from dust in molecular clouds, we propose here a new method to estimate the inclination angle of the cloud-scale magnetic field based on the statistical properties of the observed polarization fraction. We test this method using a series of Monte Carlo experiments and find that the method works well, provided that deviations of magnetic field direction from the averaged values are small. When applied to synthetic observations of numerical simulations of star-forming clouds, our method gives fairly accurate measurements of the mean magnetic field inclination angle (within 10°–25°), which can further be improved if we restrict our technique to regions of low dispersion in polarization angles ${\cal S}$ . We tested our method on the BLASTPol polarimetric observations of the Vela C molecular cloud complex, which suggests that the magnetic field of Vela C has a high inclination angle (∼60°), consistent with previous analyses.